2009
DOI: 10.1158/0008-5472.can-08-3669
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A New Class of Quinoline-Based DNA Hypomethylating Agents Reactivates Tumor Suppressor Genes by Blocking DNA Methyltransferase 1 Activity and Inducing Its Degradation

Abstract: Reactivation of silenced tumor suppressor genes by 5-azacytidine (Vidaza) and its congener 5-aza-2 ¶-deoxycytidine (decitabine) has provided an alternate approach to cancer therapy. We have shown previously that these drugs selectively and rapidly induce degradation of the maintenance DNA methyltransferase (DNMT) 1 by a proteasomal pathway. Because the toxicity of these compounds is largely due to their incorporation into DNA, it is critical to explore novel, nonnucleoside compounds that can effectively reacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(204 citation statements)
references
References 45 publications
5
195
3
1
Order By: Relevance
“…57,58 The current approach is to inhibit expression or hyperactivity of DNMT1. [59][60][61] However, demethylating agents lead to unavoidable non-specific genomic demethylation causing genomic instability, DNA damage, oncogene reactivation, and promote opportunities for cancer progression. [62][63][64][65] Because the RFTS domain functions as a key regulator of DNMT1 function, targeting RFTS interactions may revert euchromatin-associated DNMT1 activation while also normalizing pericentromeric DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 The current approach is to inhibit expression or hyperactivity of DNMT1. [59][60][61] However, demethylating agents lead to unavoidable non-specific genomic demethylation causing genomic instability, DNA damage, oncogene reactivation, and promote opportunities for cancer progression. [62][63][64][65] Because the RFTS domain functions as a key regulator of DNMT1 function, targeting RFTS interactions may revert euchromatin-associated DNMT1 activation while also normalizing pericentromeric DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Today many are described, of different nature, but few are well characterized for their mechanism of action or their selectivity towards a specific DNMT (for review Fahy et al, 2012;Gros et al, 2012). For example, SGI-1027 belongs to a family of minor groove DNA binders developed by Denny and collaborators (Datta et al, 2009) and has been shown to inhibit DNA methylation in enzymatic tests and in cancer cells. We developed two families of DNMT inhibitors: procainamide conjugates that are selective of DNA methyltransferases versus histone methyltransferases and flavanoid derivatives that also inhibit DNA methylation in an in vivo model of zebrafish development (Ceccaldi et al, 2011).…”
Section: Non-nucleoside Inhibitors For Dnmt Selectivitymentioning
confidence: 99%
“…Hypomethylating agents show [71], and some potential in MDS [72]. Several studies are currently ongoing to obtain improved efficacies of these drugs, including the development of oral preparations [73] and small molecules that can inhibit DNMTs without requiring DNA incorporation [74]. The inhibition of histone-modifying enzymes will be another potential epigenetic target for MDS therapy.…”
Section: Epigenetic Therapymentioning
confidence: 99%